Features of the composition of the intestinal microbiota in patients with colorectal cancer - S. V. Volkov; S. L. Lobanov; A. Yu. Dobrodeev (Сибирский онкологический журнал)
Purpose of the study: to investigate the composition of the intestinal microbiota and determine the feasibility of using it in diagnosis and prognosis of colorectal cancer (CRC). Material and methods. The study included 75 patients with CC (study group I) and 25 healthy individuals (control group II) who were treated at Chita State Medical Academy from 2017 to 2021. Group I patients underwent surgery and adjuvant chemotherapy. To determine the composition of the intestinal microbiota, biopsy specimens were taken from the tumor tissue and from the visually unchanged colon mucosa after the completion of surgery in the study group and from the visually unchanged colon mucosa during colonoscopy in the control group. Results. The counts of Bifidobacterium spp., E. Coli (typical) in the intestinal microbiota were significantly lower and the concentration of Clostridium spp. Was higher in CRC patients than in healthy individuals. Significant relationships between the counts of Lactobacillus spp., Bifidobacterium spp., Bacteroides spp., E. Coli and the patient’s gender; Lactobacillus spp., Bifidobacterium spp., Staphylococcus spp. (CNS) and the tumor grade; conditionally pathogenic microflora and the form of tumor growth were found. Some combinations of the composition of the intestinal microbiota in CRC patients are predictive factors for the development of postoperative complications (Lactobacillus spp., Bacteroides spp., E. Coli <3.0 CFU/g) and 3-year survival (Lactobacillus spp., Bifidobacterium spp., Bacteroides and E. Coli ≥3.0 CFU/g). Conclusion. The study of the intestinal microbiota makes it possible to differentiate patients with CRC, as well as to predict the risk of postoperative complications and patient survival.